Overcoming Problems in Pastoral Counseling for Patients with Narcissistic Disorder: Mengatasi Masalah Dalam Pendampingan Pastoral Konseling Pasien Pasien Narcissistic Disorder - Suwito , Tri Prapto; Suwandi , Markus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Man is the most perfect creature created by God among all the geniuses of living beings in this world, and God equips man with intelligence, morality and noble ethics, as well as a high culture as a sign that man is truly a creature that God has chosen as God's partner in this world, but sometimes man is born with some shortcomings such as abnormalities, Mental or physical, there are those who are physically good and perfect but mentally imperfect, there are also those who are physically imperfect but have a good and beautiful attitude. Some are born with a type of mental disorder or psychiatric disorder, although not always connate, sometimes it is an environmental influence that is formed from childhood or on the way to adulthood there are certain pressures that really affect, feelings, thoughts and thoughts that are increasingly shifting and shaping certain behaviors of a person. Mental disorders can really cause problems in life day after day. Some common types of mental disorders such as anxiety, panic, obsessive-compulsive disorder, phobias, personality disorders, stress, and other mental disorders are caused by various factors such as suffering from certain illnesses, stress due to traumatic events, the death of a loved one, loss of a job, or being isolated for a long time, as well as genetic factors inherited from parents, or environmental influences, such as disharmonious family or experiencing economic difficulties, in this case the author highlights a type of mental disorder known as Narcissistic Personality Disorder (NPD) where people with this mental disorder feel that only themselves are more important than others, so that anyone in their environment must admire or adore them. Very often people with NPD do not realize that they are the ones who have mental disorders and respond to others poorly.